Norharmane and Pterin rhenium(I) polypyridyl complexes: synthesis, structural and spectroscopic characterization - Wolcan, Ezequiel (2017)
Two novel Re(I) complexes with the general formula fac- [Re(CO)3(L)(nHo)]CF3SO3, where L = 2,2-bipyridine (bpy) or 1,10 phenanthroline (phen) and nHo (9H-pyrido[3,4-b]indole; norharmane) have been synthesized. The Re(I)-nHo complexes were characterized by structural X-ray diffraction, 1H and 13C NMR, UV-vis absorption and FT-IR spectroscopy, and by a combination of two mass spectrometry techniques, namely ESI-MS and UV-MALDI-MS.